Foreword: Whiteness As Metaprivilege - Barbara J. Flagg (Washington University Journal of Law & Policy, 2005)
Whiteness is a social location of power, privilege, and prestige. It is a “an invisible package of unearned assets.” As an epistemological stance, it sometimes is an exercise in denial. Whiteness is an identity, a culture, and an often colonizing way of life that is largely invisible to Whites, though rarely to people of color. Whiteness also carries the authority within the larger culture it dominates to set the terms on which every aspect of race is discussed and understood. Whiteness thus is many-faceted and pervasive. The papers that make up this symposium reflect the diversity of the topic. One finds here discussions of subjects ranging from the disposition of human remains to dreaming to standardized testing in schools; from patterns of informal affiliation in Senegal to self-presentation practices of individuals and of universities to September 11. Nevertheless, these seemingly dissimilar topics are linked by the strands of Whiteness as metaprivilege that run throughout.
Keywords: Critical race theory; Race preferences (Affirmative action)